2D Honeycomb‐Kagome Polymer Tandem as Effective Metal‐Free Photocatalysts for Water Splitting. Issue 21 (4th May 2021) - Jing, Yu; Zhou, Zhenpei; Geng, Weixiang; Zhu, Xinyue; Heine, Thomas
Abstract: On the basis of first‐principles calculations, the potential of applying 2D honeycomb‐kagome polymers made of heteroatom‐centered triangulene derivatives to photocatalyze water splitting is explored. The designed 2D polymers possess indirect bandgaps in the range of 1.80–2.84 eV and show pronounced light absorption in the ultraviolet and visible region of the solar spectrum. With suitable band edge alignment, the examined N‐ and B‐center polymers can generate sufficient photon‐excited electrons and holes to activate the hydrogen and oxygen evolution reactions, respectively. The combination of lattice‐inherent band features (flat bands) with chemical functionalization (potential shift due to heteroatoms) makes it possible to construct tandem cells with suppressed electron/hole recombination for effective overall water splitting. In addition, there is a potential difference between the half‐electrodes that can be utlized to power​ auxiliary components in self‐sufficient photocatalyzers. Abstract : Tandem cells made of n‐ and p‐type 2D‐HT‐polymers can be used for effective overall water splitting. Upon irradiation, the photon‐generated holes and electrons of low mobility remain in the half‐electrodes and provide sufficient drive potential to promote hydrogen and oxygen evolution. Mobile charges powered by the potential difference will enter the other half‐electrode, resulting in effective electron/hole separation.